Analisis Penerapan Akad Mudharabah Pada Pemberian Modal Pakan Ikan Berdasarkan Kajian Ekonomi Syari'ah: Dani Ahmad - Moch. Cahyo Sucipto; Rina Nurhayati; Dani Ahmad (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2019)
Analysis of the Application of Mudharabah Covenants in Fish Feed Capital Based on Sharia Economic Studies. Mudharabah agreement is a form of cooperation in moving between the owner of capital with someone called profit sharing, which is based on a sense of help and the principle of trust between the two. Because there are people who have capital, but do not have expertise in running a company. The research method used is descriptive qualitative method that is research that describes and presents an event that occurs in the field using data collection techniques that are through observation, interviews, documentation, and also library research by reading books, journals, articles, websites related to the problem to be examined. The results of this study are that the mechanism carried out in the practice of providing fish feed capital in the mechanism explained that the collaboration between the capital owner and the capital manager is mudharabah contract. If it is reviewed based on the Fatwa National Sharia Council number: 115/DSN-MUI /IX/2017 concerning mudharabah agreements that the provision of fish feed capital is included in the mudharabah agreements and is legal (allowed). In the agreement the manager may not sell fish that are ready to harvest to other parties. However, that management guy is cooperating with PD. Bangun Jaya Fish Farm that is those harvesting fish are sold to others.